E3 ligase ligand optimization of Clinical PROTACs - Jiang, Hanrui; Xiong, Huan; Gu, Shuang-Xi; Wang, Mingliang (Frontiers in Chemistry, 2023)
Proteolysis targeting chimeras (PROTACs) technology can realize the development of drugs for non-druggable targets that are difficult to achieve with traditional small molecules, and therefore has attracted extensive attention from both academia and industry. Up to now, there are more than 600 known E3 ubiquitin ligases with different structures and functions, but only a few have developed corresponding E3 ubiquitin ligase ligands, and the ligands used to design PROTAC molecules are limited to a few types such as VHL, CRBN, MDM2, IAP, etc. Most of the PROTAC molecules that have entered clinical trials were developed based on cereblon ligands, and only DT2216 was based on VHL ligand. Obviously, the structural optimization of E3 ubiquitin ligase ligands play an instrumental role in PROTAC technology from bench to bedside. In this review, we review the structure optimization process of E3 ubiquitin ligase ligands currently entering clinical trials on PROTAC molecules, summarize some characteristics of these ligands in terms of druggability, and provide some preliminary insights into their structural optimization. We hope that this review will help medicinal chemists to develop more druggable molecules into clinical studies and to realize the greater therapeutic potential of PROTAC technology.